ASPIRASI KE AKSI: ANALISIS SEM (STRUCTURAL EQUATION MODELING) FAKTOR PENENTU MINAT SISWA LANJUT PERGURUAN TINGGI - Yulianto, Yulianto; Toto, Yusron; Saryono, Udin; Sukmawati, Taryati; Rizaldy, Rizaldy; Yuniarti, Yuniarti; Megawati, Megawati; Apriani, Tia (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of parental support, intrinsic and extrinsic motivation, educational self-efficacy, access to college information, and socioeconomic status on students' interest in continuing their education to college. In addition, this study examines the mediating role of self-efficacy as well as the interaction between these factors in the Indonesian context. The study used a quantitative approach with a survey method through a closed questionnaire based on a 5-point Likert scale. The findings provide new insights into the complexity of the determinants of interest in higher education in Indonesia, particularly the negative role of excessive parental support and the inconsistent influence of self-efficacy. The practical implications include the need for a more holistic approach in educational policies and counseling guidance programs involving parents and students. This study also fills a gap in the literature by examining the unique interaction between psychological, social and contextual factors in the Indonesian context, while questioning the universal assumption of a linear relationship between parental support and educational motivation. The findings on the negative effects of information overload also make a novel contribution to the literature discussion on educational decision-making.